Changing the obesogenic environment to improve cardiometabolic health in residential patients with a severe mental illness: cluster randomised controlled trial. (November 2017) - Looijmans, Anne; Stiekema, Annemarie P. M.; Bruggeman, Richard; van der Meer, Lisette; Stolk, Ronald P.; Schoevers, Robert A.; Jörg, Frederike; Corpeleijn, Eva
Abstract : Background: For patients with severe mental illness (SMI) in residential facilities, adopting a healthy lifestyle is hampered by the obesity promoting (obesogenic) environment. Aims: To determine the effectiveness of a 12-month lifestyle intervention addressing the obesogenic environment with respect to diet and physical activity to improve waist circumference and cardiometabolic risk factors v. care as usual (Dutch Trial Registry: NTR2720). Method: In a multisite cluster randomised controlled pragmatic trial, 29 care teams were randomised into 15 intervention (365 patients) and 14 control teams (371 patients). Intervention staff were trained to improve the obesogenic environment. Results: Waist circumference decreased 1.51 cm (95% CI −2.99 to −0.04) in the intervention v. control group after 3 months and metabolic syndrome z-score decreased 0.22 s.d. (95% CI −0.38 to −0.06). After 12 months, the decrease in waist circumference was no longer statistically significantly different (–1.28 cm, 95% CI −2.79 to 0.23, P = 0.097). Conclusions: Targeting the obesogenic environment of residential patients with SMI has the potential to facilitate reduction of abdominal adiposity and cardiometabolic risk, but maintaining initial reductions over the longer term remains challenging.